Beam characterizations at femtosecond electron beam facility - S. Rimjaem (2018)
The SURIYA project at the Fast Neutron Research Facility (FNRF) has been established and is being commissioning to generate femtosecond (fs) electron bunches. Theses short bunches are produced by a system consisting of an S-band thermionic cathode RF-gun, an alpha magnet (α-magnet) serving as a magnetic bunch compressor, and a SLAC-type linear accelerator (linac). The characteristics of its major components and the beam characterizations as well as the preliminary experimental results will be presented and discussed in this paper. © 2005 IEEE.